LPS-induced mitochondrial dysfunction regulates innate immunity activation and α-synuclein oligomerization in Parkinson's disease - Esteves, A. Raquel (2023)
Sporadic Parkinson's disease (sPD) is a complex multifactorial disorder which etiology remains elusive. Several mechanisms have been described to contribute to PD development namely mitochondrial dysfunction, activation of inflammatory pathways and the deposition of unfolded proteins such as α-synuclein. Our work shows for the first time that lipopolysaccharide (LPS)-induced activation of innate immunity requires a functional mitochondria and mimics PD pathology in cells. We found in primary mesencephalic neurons that LPS targeted the mitochondria and activated neuronal innate immune responses, which culminated with α-synuclein oligomerization. Moreover, in cybrid cell lines repopulated with mtDNA from sPD subjects with inherent mitochondrial dysfunction and NT2-Rho0 obtained by long-term ethidium bromide exposure, and so without a functional mitochondrial, LPS was not able to further activate innate immunity or increase α-synuclein aggregation. Herein, we showed that mesencephalic neurons are able to activate innate immunity after LPS exposure and this pathway is dependent on mitochondria. Moreover, we disclose that α-synuclein over production is an innate immune response. Our data indicate that mitochondria provide the base for innate immunity activation in idiopathic PD.